Investigating the Teachers’Attitude Regarding open Educational Resources (OER) at Sukhothai Thamathirat Open University, Thailand - Jeetendra Pande; Alka Singh; Kamolrat Intaratat; G. Mythili (Research Highlights in Language, Literature and Education Vol. 1, 2022)
The Open Educational Resource (OER) culture encourages teachers to absorb existing OER, adapt, and share with others in order to maintain the circle of collaboration and ongoing improvement. Understanding instructors’ attitudes about OER use and comparing data across institutions may aid in identifying issues that influence OER adoption. The primary goal of this work is to investigate teachers’ attitudes regarding open educational resources (OER) at Sukhothai Thamathirat Open University (STOU) in Thailand. In this study, the teachers’ attitude toward OER was measured using a five-point scale ranging from strongly disagree to highly agree. Adaptation and use of OER, as well as sharing of OER, can be detected based on the scale. The questionnaire was distributed to the STOU faculty. There were 32 STOU respondents included for analysis. Data was collected via an online form. The data was statistically examined using statistical methods. Along with the chi-square test, frequency measurements were employed to depict demographic and other data. SPSS was used for the analysis. Teachers in Thailand are encouraged to share OER for professional development and personal fulfilment. It is interesting to note that the vast majority of them are driven to share and contribute to OER in order to spread ideas in a knowledge society.